The Impact of Smartphone Restrictions on Elementary School Students' Interest in Learning - Tiara Nurani Suswandi; Siti Ripandi (Indonesian Journal of Innovative Teaching and Learning, 2024)
Background: The widespread use of smartphones among elementary school students has raised concerns about its potential impact on their academic engagement and motivation. Excessive smartphone usage may lead to distractions that negatively affect students' interest in learning. Objective: This study aimed to examine the effect of limiting smartphone use on students’ learning interest in primary school. Method: The research employed an ex post facto design conducted at SDI Daar Al Iman in 2021. A total of 31 students participated in the study. Data were collected using two scales: one measuring smartphone use restrictions and the other measuring learning interest. The data were analyzed using simple linear regression. Result: The t-test results indicated a significant effect, with a p-value of 0.000, which is less than 0.05 (0.000 < 0.05). This finding suggests a statistically significant influence of limiting smartphone usage on students' learning interest. Conclusion: The study concludes that restricting smartphone use has a positive effect on enhancing students' interest in learning at school. Contribution: The findings of this study provide theoretical and practical insights for teachers, readers, and future researchers, offering a novel perspective on managing technology use to support academic motivation in primary education.